Effect of Various Organic Fertilizer Treatments on Soil Bulk Density and Soil Color in Yardlong Bean (Vigna sinensis L.) - B. Hamsa, Jamaludin; Nurmi; S. Bagu, Fitria; Zulzain Ilahude; Yunita Rahim (International Journal of Technology and Education Research, 2026)
Yardlong bean (Vigna sinensis L.) is one of the secondary food crops with considerable potential as a food source; th erefore, improvements in cultivation practices are required to enhance its productivity. One effort to increase yardlong bean production is through the application of organic fertilizers, such as chicken manure and cattle manure. This study aimed (1) to evaluate the effects of chicken manure and cattle manure application on soil bulk density (BD) and soil color in yardlong bean cultivation, and (2) to determine the optimal dosage of these organic fertilizers for improving BD and soil color. The study was conducted from September to January 2026 in Tunggulo Village, Tilong Kabila Subdistrict, Bone Bolango Regency, Gorontalo Province, Indonesia. The experiment employed a Randomized Block Design (RBD) consisting of five treatments: P0 (control, without fertilizer), P1 (chicken manure at 10 t ha⁻¹), P2 (chicken manure at 20 t ha⁻¹), P3 (cattle manure at 10 t ha⁻¹), and P4 (cattle manure at 20 t ha⁻¹). Data were analyzed using analysis of variance (ANOVA) followed by the Honestly Significant Difference (HSD) test, and correlation analysis was conducted to examine the relationship between BD and the growth and yield of yardlong bean. The results indicated that the application of chicken manure and cattle manure had no significant effect on soil bulk density and soil color.